(untitled)
Unification fundamentally changed the terms of quantitative macroeconomic analysis for Germany. Two main areas concerned are data availability for the eastern part of Germany and structural changes within the behavioural equations after unification. Our paper presents results from the estimation of a macroeconometric disequilibrium model formerly developed for West Germany. The challenge is to handle the structural break in the time series and the economic model by applying a SUR estimator for West Germany and the Federal Republic of Germany, respectively. The main focus here is the modeling of investment expenditures and employment adjustment. The empirical results are encouraging and show that the disequilibrium model is flexible enough to analyze the changes induced by unification. In particular, our results reveal that most behavioural relationships remained fairly stable when switching from West Germany to the Federal Republic of Germany. One notable exception is investment behaviour which during the first years after unification was strongly affected by fiscal incentives in East Germany. Preliminary policy simulations show effects of these fiscal incentives and the demand shock to the West German economy. The simulated responses depend on the prevailing regimes on goods and labour markets. – – Die deutsche Wiedervereinigung veränderte die Ausgangslage für makroökonometrische Analysen. Dies betrifft zum einen die Verfügbarkeit von Daten in Ostdeutschland, zum anderen die in Folge der Wiedervereinigung bedingten strukturellen Veränderungen in den Verhaltensgleichungen. Diese Studie zeigt die Schätzergebnisse eines makroökonometrischen Ungleichgewichtsmodells, das für Westdeutschland entwickelt wurde. Zum einen bestand die Herausforderung darin, eine Lösung für den Strukturbruch in den Zeitreihen zu finden, zum anderen darin, die strukturellen Veränderungen in den Modellgleichungen mittels eines SUR-Ansatzes für West- und Gesamtdeutschland abzubilden. Den Schwerpunkt dieses Beitrags bildet die Modellierung der Investitionen und der Beschäftigungsanpassung. Die Ergebnisse zeigen, dass das Ungleichgewichtsmodell flexibel genug ist, um die Veränderungen infolge der deutschen Wiedervereinigung zu analysieren. Die meisten Verhaltensgleichungen bleiben bei dem Übergang von West- zu Gesamtdeutschland stabil. Eine Ausnahme bildet das durch die Öffentlichen Fördermittel beeinflusste Investitionsverhalten. Vorläufige Simulationen untersuchen die Wirkungen des vereinigungsbedingten Nachfrageschocks im Westen sowie der Öffentlichen Fördermassnahmen im Osten. Die Simulationsergebnisse hängen von den jeweils vorherrschenden Regimen auf dem Arbeits- und Gütermarkt ab., address = Mannheim, author = Peter Winker and Werner Smolny and Daniel Radowski, copyright = http://www.econstor.eu/dspace/Nutzungsbedingungen, keywords = E22; C51; E24; 330; Ökonometrisches Makromodell; Ungleichgewichtstheorie; Nationale Einheit; Strukturbruch; Schätzung; Theorie; Deutschland; Neue Bundesländer, language = eng, number = 99-61, publisher = Zentrum für Europäische Wirtschaftsforschung (ZEW), title = Modeling German unification in a disequilibrium framework, type = ZEW Discussion Papers, url = https://hdl.handle.net/10419/24343, year = 1999